Grain yield and baking quality of wheat under different sowing dates (Acta Scientiarum. Agronomy, 2014)
Choosing the right sowing dates can maximize the outcomes of the interaction between genotype and environment, thus increasing grain yield and baking quality of wheat (Triticum aestivum L.). The present study aimed at determining the most appropriate sowing dates that maximize grain yield and baking quality of wheat cultivars. Seven wheat cultivars (BRS 179, BRS Guamirim, BRS Guabiju, BRS Umbu, Safira, CD 105 and CD 115) were evaluated at four sowing dates (the 1st and the 15th of June and July) in two harvesting seasons (2007 and 2008). The study was setup in a completely randomized block design with four repetitions. The effects of the year and sowing date when combined explained 93% of the grain yield variance. In 2007, the CD 105 and Safira cultivars had the highest grain yield (GY) for all sowing dates. Only the BRS Guabiju and Safira cultivars possessed high baking quality for all sowing dates assessed. In 2008, the environmental conditions were favorable for superior GY, but the baking quality was inferior. Considering adapted cultivars and sowing dates, it is possible to maximize grain yield and baking quality of wheat.